1999
DOI: 10.1016/s0165-2427(99)00059-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of immunologic diseases of the dog

Abstract: The following review is based on notes used in the teaching of clinical immunology to veterinary students. Immune diseases of the dog are placed into six different categories: (1) type I or allergic conditions; (2) type II or auto- and allo-antibody diseases; (3) type III or immune complex disorders; (4) type IV or cell-mediated immune diseases; (5) type V conditions or gammopathies; and (6) type VI or immunodeficiency disorders. Separate discussions of transplantation immunology and the use of drugs to regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 284 publications
(226 reference statements)
1
58
0
11
Order By: Relevance
“…Considering both female sex categories together, the proportion of females diagnosed with these immune conditions was slightly greater than when compared to the aggregate male data. A 1999 review by Pedersen reported the greatest prevalence of immune conditions occurred in intact females and the lowest with intact males [32] an assertion supported by the human literature [46] although those previous reports focused solely on intact individuals. In the canine literature, diagnoses of atopic dermatitis [47], CMG [20], IBD [48], lupus erythematosus [49], and PEMC [50] do not exhibit sex differences whereas for ADD, AIHA, IMPA, and ITP females have approximately a twofold higher risk than males [24, 51, 52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering both female sex categories together, the proportion of females diagnosed with these immune conditions was slightly greater than when compared to the aggregate male data. A 1999 review by Pedersen reported the greatest prevalence of immune conditions occurred in intact females and the lowest with intact males [32] an assertion supported by the human literature [46] although those previous reports focused solely on intact individuals. In the canine literature, diagnoses of atopic dermatitis [47], CMG [20], IBD [48], lupus erythematosus [49], and PEMC [50] do not exhibit sex differences whereas for ADD, AIHA, IMPA, and ITP females have approximately a twofold higher risk than males [24, 51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Lupus erythematosus included diagnoses of both systemic lupus erythematosus (SLE) and discoid lupus erythematosus (DLE) based upon the view that DLE is a localized presentation of SLE [32]. Pyometra (PYO) was used as a positive control; pyometras recorded for neutered females were stump pyometras.…”
Section: Methodsmentioning
confidence: 99%
“…It seems to be a problem of civilization connected with rising environmental pollution. The fact that our pets spend much more time indoors exposed to dust mite antigens is also a possible reason for the increased prevalence of atopic dermatitis (Pedersen 1999). In the field of human medicine, the 'hygiene hypothesis' and 'western' life style contribute to the allergic immunological profile (Th2 lymphocytes domination) (Lasek 2005;Roosje 2005).…”
mentioning
confidence: 99%
“…Επειδή η νό σος, σε αντίθεση με τον άνθρωπο, εμφανίζεται σπάνια στο σκΰλο, δεν υπάρχουν αξιόπιστα δεδομένα αναφορικά με την προδιάθεση ως προς τη φυλή και το φΰλο (Iwasaki et al 1995, Rivierre andOlivry 2004). Ορισμένοι, όμως, ερευ νητές αναφέρουν ότι τέτοια προδιάθεση έχει διαπιστωθεί στις φυλές Collie, Shetland sheepdog και Doberman pinscher (Pedersen 1999). Πρόκειται για δερματοπάθεια των νεαρών και νεαρών ενήλικων κυρίως ζώων, η κλινι κή εικόνα της οποίας χαρακτηρίζεται από φυσαλίδες, διαβρώσεις, έλκη και εφελκίδες, με κυρίες εντοπίσεις την εσωτερική επιφάνεια των πτερυγίων των αυτιών, την κοι λιακή χώρα, τις μασχάλες, τα βλεννογονοδερματικά όρια και το βλεννογόνο της στοματικής κοιλότητας (Pedersen 1999, Olivry and Chan 2001, Scott et al2001).…”
Section: πομφολυγωδες πεμφιγοειδεςunclassified